To catch a killer [videorecording (DVD)] - Szifron, Damián, 1975-; Wakeham, Jonathan; Woodley, Shailene; Mendelsohn, Ben; Adepo, Jovan; Ineson, Ralph, 1969- (Vertical Entertainment, 2023)
Baltimore. New Year's Eve. A talented but troubled police officer is recruited by the FBI's chief investigator to help profile and track down a disturbed individual terrorizing the city.